Revision of the Ecuadorian Microstigmatidae (Araneae: Mygalomorphae), with the description of six new species - Nadine Dupérré; Elicio Tapia (European Journal of Taxonomy)
The small mygalomorph family Microstigmatidae Roewer, 1942 from Ecuador is reviewed, and images of the blind cave species, Spelocteniza ashmolei Gertsch, 1982 are presented. Six new species are described, and one new genus is erected: Pseudonemesia scutata sp. nov. (♂), Spelocteniza pampenita sp. nov. (♂♀), Spelocteniza zuninoi sp. nov. (♂), and Pastaza gen. nov., Pastaza aureliae gen. et sp. nov. (♀), Pastaza roberti gen. et sp. nov. (♂♀) and Pastaza vegai gen. et sp. nov. (♂). SEM images of the cuticle and tarsal organ of all genera are provided, and finally, the presently recognised diagnostic characteristics of the family are discussed.